Is Lateral Femoral Nailing Associated With Increased Intensive Care Unit Days? A Propensity-Matched Analysis of 848 Cases. Issue 1 (January 2018) - Reahl, G. Bradley; O'Hara, Nathan N.; Coale, Max; O'Hara, Lyndsay M.; Castillo, Renan; O'Toole, Robert V.; Slobogean, Gerard P.
Abstract : Objective: The purpose of this study is to determine if lateral patient position during femoral nailing is associated with increases in intensive care unit (ICU) length of stay (LOS) or ventilator days when compared with femoral nailing in a supine position. Design: Retrospective cohort study. Setting: Level 1 trauma center. Patients/Participants: Patients with femoral shaft fractures treated with intramedullary fixation were identified. Propensity matching was performed to minimize selection bias using factors thought to be associated with surgeon selection of supine nailing at our institution (Injury Severity Score, Abbreviated Injury Score brain, and bilateral fractures). After matching, 848 patients were included in the analysis. Intervention: Femoral nailing in the lateral position compared with the supine position. Main Outcome Measurements: Our primary outcome measure was ICU LOS. Ventilator days were the secondary outcome. Results: Treating patients with femoral nailing in the lateral position was associated with a 1.88 days (95% confidence interval, 0.73–3.02; P = 0.001) reduction in ICU LOS in our adjusted model. Intramedullary nailing in the lateral position was associated with a 1.29 days (95% confidence interval, −0.12 to 2.69) decrease in postoperative time on a ventilator. However, this finding was not statistically significant ( P = 0.07). Conclusion: Lateral femoral nailing was associated with decreased ICU LOS ( P = 0.001) even after accounting for selection bias using propensity score matching. Our data indicate that lateral femoral nailing is likely not associated with the increased risk of pulmonary complication. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.